2010
DOI: 10.1104/pp.110.166330
|View full text |Cite
|
Sign up to set email alerts
|

Callose Synthase GSL7 Is Necessary for Normal Phloem Transport and Inflorescence Growth in Arabidopsis    

Abstract: One isoform of callose synthase, Glucan Synthase-Like7 (GSL7), is tightly coexpressed with two isoforms of sucrose synthase (SUS5 and SUS6) known to be confined to phloem sieve elements in Arabidopsis (Arabidopsis thaliana). Investigation of the phenotype of gsl7 mutants of Arabidopsis revealed that the sieve plate pores of stems and roots lack the callose lining seen in wild-type plants. Callose synthesis in other tissues of the plant appears to be unaffected. Although gsl7 plants show only minor phenotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 68 publications
10
136
1
Order By: Relevance
“…Whether those developmental processes are regulated by specific GPI-APs or through changes in callose deposition is a question for the future. The callose lining in sieve plate pores is essential for normal phloem transport and as a result for the movement of FLOWERING LOCUS T (Barratt et al, 2011;Rinne et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Whether those developmental processes are regulated by specific GPI-APs or through changes in callose deposition is a question for the future. The callose lining in sieve plate pores is essential for normal phloem transport and as a result for the movement of FLOWERING LOCUS T (Barratt et al, 2011;Rinne et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent research reported that the AtGSL7 gene functioned to synthesize callose in the phloem sieve plates (Barratt et al, 2011;Xie et al, 2011). To examine callose deposition at sieve plates and in response to wounding, we performed aniline blue staining.…”
Section: Pd Appear Unaffected In Tdy2 Veinsmentioning
confidence: 99%
“…Callose has been shown to be involved in the regulation of the sieve pore diameter. In cals7 mutants reduced callose deposition at the sieve plate leads to a reduced number of open pores per sieve plate, smaller diameter sieve pores and impaired phloem transport 22,23 . But also over accumulation of callose, as shown by the phloem-specific expression of a gain of function mutant of CalS3, inhibits phloem conductivity 24 , suggesting that callose deposition at the sieve plate has to be tightly regulated.…”
mentioning
confidence: 99%